Obstacles of Applying E-Training in the Training and Professional Development Centers in the Sultanate of Oman from the Point of View of the Trainers - Al-Makhashni, Sulaiman Khalaf Saeed; Hamid, Jamilah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the obstacles to the application of e-training in training and professional development centers in the Sultanate of Oman from the point of view of the study sample of trainers, their assistants and training specialist, the researcher took the descriptive approach to his study and took identification as a tool for gathering data and information, consisting of (36) items distributed over the fields of study. After verifying its truthfulness and stability, it was applied to the members of the study sample, which consisted of (174) trainers, their assistants and training specialists in the training and professional development centers. The most important findings of the study were the degree of the existence of obstacles to the application of e-training in training and professional development centers in the point of view of the study sample came to a large extent in general, the degree of constraints related to the financial and technical aspects was greater than the obstacles related to the human side, and the absence of statistically significant differences at the function level of (0.05) between the estimates of the sample members of the obstacles to the application of e-training in training and professional development centers attributed to the variable of years of experience, Most important of which are, The Ministry of Education, in coordination with the concerned telecommunications authorities, fixes the technical problems of the Internet in the training centers and work to increase the speed of the network, and allocate an adequate budget to the training centers to enable them to provide tools and supplies related to the employment of e-training.